1985
DOI: 10.1002/zaac.19855260711
|View full text |Cite
|
Sign up to set email alerts
|

Über die thermischen Eigenschaften von Heteropolysäuren des Typs H3+n[PVnMo12−nO40] · x H2O (n = 0, 1, 2, 3) I. Thermogravimetrische, UV‐VIS‐ und röntgenographische Untersuchungen

Abstract: Das thermische Verhalten der Dodecamolybdophosphorsäure und ihrer vanadiumhaltigen Homologen, in Substanz und aufgebracht auf SiO2‐Träger, wird mittels DTA/TG, thermogravimetrisch, sowie UV‐Vis‐spektroskopisch und röntgenographisch untersucht. Bei etwa 450 K liegen die kristallwasserfreien Verbindungen vor, bis zu etwa 630 K wird das gesamte Konstitutionswasser abgegeben, ohne daß dabei ein Zusammenbruch der Kegginstruktur erfolgt. Dies ergibt sich aus der Rehydratisierbarkeit der „Anhydride”︁ durch Wasserdamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 10 publications
3
11
0
Order By: Relevance
“…This observation is inline with the work of Marchal-Roch et al [12] who reported the TG analysis of (NH 4 ) 3 PMo 12 O 40 and mixed ammonium and Cs salts. Bruckman et al [26] have also reported the thermal behavior of pure and silica-supported vanadium substituted MPA catalysts and revealed that the thermal stability is high with supported catalyst compared to that of the bulk catalyst.…”
Section: Thermogravimetric/differential Thermal Analysis (Tg/dta) Stumentioning
confidence: 94%
See 1 more Smart Citation
“…This observation is inline with the work of Marchal-Roch et al [12] who reported the TG analysis of (NH 4 ) 3 PMo 12 O 40 and mixed ammonium and Cs salts. Bruckman et al [26] have also reported the thermal behavior of pure and silica-supported vanadium substituted MPA catalysts and revealed that the thermal stability is high with supported catalyst compared to that of the bulk catalyst.…”
Section: Thermogravimetric/differential Thermal Analysis (Tg/dta) Stumentioning
confidence: 94%
“…The results obtained and the conclusions drawn in some cases, like 12-molybdophosphoric acid on silica as mentioned by Claude Rocchccioli-Deltcheff [25] are quite contradictory. It is reported that the thermal stability of MPA decreased when it is supported on silica and the stability of catalyst is less at lower concentration of MPA [26,27]. Servicka et al [28] concluded that deposition on silica lowers the stability of MPA.…”
Section: Introductionmentioning
confidence: 99%
“…This means that average value < x > in a crystalline hydrate is smaller than the value of x in the initial HPA‐ x (see Table 1). 86,87…”
Section: Composition Of Aqueous Mo‐v‐p Hpa Solutionsmentioning
confidence: 99%
“…[9] Incorporating Vatoms in bulk HPOM leads to adecreasing thermalstability. [10] Keggin ions partially decompose under catalytic conditions above 573 Kt of orml acunary Keggin anionsi nw hich Mo cations migrate to extra Keggin ion sites. Driving force for the formation of lacunary Keggina nions may be the relaxation of the Keggins tructure at an elevated temperature upon removal of structural water.S ubsequently,l inks are formedb etween Keggin ions, which eventually resulted in more extended oxide structures.…”
Section: Introductionmentioning
confidence: 99%